Transmission of Islamic reform from Egypt to Malaysia: a study of Hasan Al-Bana’s legacy - Mamat, Ismail (Zes Rokman Resources, 2016)
One of the most well known personalities in Muslim society of the twentieth century was Hasan al-Banna (1906-1949). He was the founder of JamÉÑat al-IkhwÉn al-MuslimÊn (the Muslim Brotherhood), one of the influencial Muslim organizations in Egpyt. His ideas made a great impact on the Islamic movements in the world especially after nineteenth century until today.This paper aims to analyze the influence of Hassan al-Banna into the Islamic Movements in Malaysia particularly Parti Islam se Malaysia (the Islamic Party of Malaysia) (PAS) and Angkatan Belia Islam Malaysia (the Muslim Youth Movement of Malaysia) (ABIM). Islamic movements actually call for a total Islamic reform in the life of the individual, family, society and social, economic, political, legal, educational and cultural systems. They call for a holistic understanding of Islam which is not reduced to intellectual, economic, or social activities of people.Results show that Hassan al-Banna was one of the most important figures who were responsible for shaping those Islamic Movements in Malaysia.